Relationships of Age and Gender with Ankle-brachial Systolic Pressure Index and Cardio-ankle Vascular Index in Patients with Diabetes Mellitus - Mikio Marumo; Shigeyuki Ebara; Ikumi Nishibe; Jun-ichi Soneda; Ichiro Wakabayashi (International Journal of Gerontology, 2018)
Summary: Background: Cardio-ankle vascular index (CAVI) and ankle-brachial systolic pressure index (ABI) are used as indicators of atherosclerotic progression, which is more prominent in the elderly than in the young. The relationships of age and gender with these indicators were investigated in patients with diabetes mellitus. Methods: Subjects were outpatients with type 2 diabetes (113 men and 53 women). CAVI and ABI were simultaneously measured at rest. ABI was also measured after leg exercise. Patients with ABI higher than 1.3 were excluded from the subjects. Results: CAVI and ABI were significantly higher in men than in women, while % decrease in ABI after exercise was not significantly different in men and women. Both in men and women, CAVI was not significantly correlated with ABI and % decrease in ABI. Both in men and women, there were significant correlations between age and CAVI (men, r = 0.497 [p < 0.01]; women, r = 0.480 [p < 0.01]). In men, age did not show significant correlations with ABI (r = −0.167) and % decrease in ABI after exercise (r = 0.129). In women, age showed a significant correlation with ABI (r = −0.280 [p < 0.05]) but not with % decrease in ABI after exercise (r = 0.020). Conclusion: In male and female patients with diabetes, ABI was not associated with CAVI. Age was related more strongly with CAVI than with ABI. Thus, CAVI is thought to be a more reliable marker than ABI for atherosclerotic progression in patients with diabetes. Keywords: ABI, Aging, Atherosclerosis, CAVI, Diabetes mellitus